ANALISIS RETRIBUSI PARKIR TERHADAP PENDAPATAN ASLI DAERAH DAN DAMPAKNYA TERHADAP PENGEMBANGAN SARANA DAN PRASARANA DI KABUPATEN BANDUNG - Maryani, Riah (EKSPANSI, 2017)
Abstract: This research was conducted with the aim to know how the process of parking levy management in Bandung regency, what are the obstacles experienced in the management so far, and the process of revenue into local revenue (PAD) which is beneficial to the development of facilities and infrastructure in Bandung regency. The research method used is descriptive verifikatif and the type of data used is secondary. Analysis of research data is done by using the method of Multiple Linear Regression and Path Analysis (Path Analysis). The statistical test in this study used F-Test, T-Test and Classic Assumption Test. The result of regression analysis shows that R2 reaches 0.409. It shows that only 40.9% of variable of Original Regional Income (PAD). While according to path analysis obtained result of calculation which show that indirect influence only equal to 0.39104 or about 39.104%. The conclusions of the research are as follows: (i) Parking charges have no significant effect on PAD. (Ii) PAD has no significant effect on the development of facilities and infrastructure. (Iii) There is no significant effect of parking levy on the development of facilities and infrastructure through PAD. Keywords: Parking Charge, Local Income, Fasilities and Infrastructure